Improved heterocyclic aromatic hydrocarbon compound adsorption using functionalised rice husk biochar - Azman, Nur Azzyyati; Mohd Fuzi, Siti Fatimah Zaharah; Abdul Manas, Nor Hasmaliana; Wan Azelee, Nur Izyan; Nasratun Masngut, Nasratun Masngut (Elsevier, 2024)
Carbazole (CBZ) is a hazardous heterocyclic aromatic hydrocarbon (HAH) that pollutes water bodies, and the treatment remains a challenge due to its high persistence in the environment. This study chemically modified rice husk biochar (RHB) with starch derivative (DS) to develop an effective adsorbent. Thus, functionalised RHB with starch derivative (RHBDS) was synthesised to remove CBZ from synthetic wastewater. Based on a Box-Behnken design, the DS functionalisation optimisation was successfully performed. The parameters, including RHB mass of (5–10) g, DS concentration of (1–5)% w/v, and sonication period of (1–5) min, were analysed using Design Expert. These parameters were then utilised to investigate the optimal conditions (removal rate response and adsorption capacity) for the adsorbent. The removal rate and the adsorption capacity ranged from 83.85 to 98.94 % and 335.41 to 395.76 mg/g, respectively. Consequently, the RHB mass of 6.50 g, DS concentration of 1 % w/v, and sonication period of 5 min within the experimental domain exhibited the best conditions with desirability of 1.0. The 92.67 % removal rate and adsorption capacity of 370.59 mg/g were also obtained under optimal conditions. Compared to RHB, RHBDS demonstrated four times the adsorption capacity for the CBZ removal from synthetic water, which were 23.03 mg/g and 98.01 mg/g, respectively. Therefore, the RHBDS compound could be a promising adsorbent in removing CBZ from wastewater.